The Reflections of Sufism and the Love for Ali on Personal Names in the Sanjaks of Eleskird, Selve, Diyadin, Bayezid and Ovacik in the 16th Century (Journal of Alevism-Bektashism Studies, 2019)
This paper has determined the names of people living in the sanjaks of the province of Agri from the archival documents of the Ottoman period and is presented for the benefit of those who are interested in the subject. The paper has assessed the names of Muslims in the cadastral record book number 199 in the Archive of Kuyud-i Kadime of the General Directorate of Land Registry and Cadastre in Ankara, dated 1578. This paper draws attention to the fact that Sufism and the love for Ali stand out in the personal names of taxpayers living in the above-mentioned sanjaks. The signs of the love for Ali are clearly seen in some personal names, such as Ali, Alican, Ali Gazi, Ali Kulu, Ali Yar, Ayvad Ali, Bayram Ali, Borc Ali, Bürhan Ali, Cafer Ali, Can Ali, Derviş Ali, Devlet Ali, Dost Ali, Dur Ali, Emir Ali, Emirze Ali, Esed Ali, Genc Ali, Gürd Ali, Gonca Ali, Gulam Ali, Güher Ali, Gül Ali, Hasan Ali, Haydar Ali, Hoca Ali, Hüseyin Ali, Hub Ali, Koç Ali, Kul Ali, Mahmud Ali, Masum Ali, Maksud Ali, Mehmed Ali, Merd Ali, Mervan Ali, Mihmad Ali, Mirza Ali, Muhib Ali, Murad Ali, Nur Ali, Pir Ali, Sefer Ali, Seydi Ali, Sultan Ali, Şah Ali, Şeyh Ali, Şükür Ali, Ulu Ali, Yar Ali, and in some personal names, such as Haydar, Haydar Kulu, İmam Kulu, İmam Verdi, Mirza Han, Şah Kulu, those signs are indirect. We have observed, from the data in the cadastral record book that we analysed, that the personal names related to Sufism prevail, too. The main ones are Abdal, Ağyar, Baba, Babacan, Baba Kulu, Balım, Dede, Dede Can, Dem Kulu, Derviş, Derviş Can, Halvet, Hızır, Mehdi, Mehdi Kulu, Muhib, Muhib Kulu, Mürşid Kulu, Nazar, Niyaz, Nefes, Nefes Kulu, Niyaz, Niyaz Kulu, Pervane, Pir Dost, Pir Makam, Pir Sultan, Pür Niyaz, Rıza Kulu, Sahib, Sahib Kulu, Sultan Kulu, Şah Bende, Şah Veled, Şah Nazar, Şah Veli, Şah Verdi, Tabduk, Tevelli, Ulu Can, ‘Uryan (Üryan), ‘Uryan Kulu, Yol Kulu, Zakir and Zülfikar. These determined names of people were also given to the villages where they lived. In addition, it will be possible to see all the names of people and places in the sanjaks of Eleskirt, Selve, Diyadin, Ovacik and Beyazid (Dogubeyazit) in 1578, in the given alphabetical order of the names determined in terms of the prevalence of personal names. Based on the data from the cadastral record books, this paper reveals the effects of Sufism and the love for Ali on Turkish names of people and places.